PEMBERDAYAAN MASYARAKAT PRASEJAHTERA MELALUI BERAS SEJAHTERA DI DESA TONGKO KECAMATAN BAROKO KABUPATEN ENREKANG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This research raises the problem of “how is social empowerment through welfare rice assistance for underprivileged families in Tongko Village, Baroko District, Enrekang Regency”, with sub-problems, namely: how is the process of social empowerment through welfare rice assistance for underprivileged families in Tongko Village, Baroko District, Enrekang Regency? And how to get involved in the process of social empowerment through welfare rice assistance for underprivileged families in Tongko Village, Baroko District, Enrekang Regency? This research uses descriptive qualitative research which is located in Tongko Village, Baroko District, Enrekang Regency. The research approach used is a psychological approach, a sociological approach, and the primary data source of this research is the village head (key informant), additional information, namely underprivileged families, prosperous rice aid recipients but not including underprivileged families and the community (assessor) of prosperous rice. Secondary data sources are books, magazines, newspapers, and other data sources that can complement the data. Data methods are observation, in-depth interviews, and documentation, Data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. The results showed that, the process of social empowerment through prosperous rice for underprivileged families in Tongko Village, Baroko District, Enrekang Regency, namely, the social preparation stage, the program implementation, and control stage, and the monitoring and evaluation program stage. Obstacles in the process of social empowerment through prosperous rice for underprivileged families in Tongko Village, Baroko District, Enrekang Regency, namely the data collection system is still nepotic, and the problem of leveraging and validating data. The implication of this research is that the village government and its staff are transparent in relation to the issue of assistance from the government, directed at the state which collects the data evenly to the community.